The Development of Inductive Approach for Artistic Creativity Encouragement Based on Lesson Study: A Case Study of Product Design for Mattayomsuksa 3 (Grade 9) Students - Vadhanabhu, Narit (Fine Arts Journal: Srinakharinwirot University, 2015)
This study aims 1) to develop inductive approach for encouraging artistic creativity emphasizing on product design of Mattayomsuksa 3 (Grade 9) students based on lesson study, 2) to examine student’s learning achievement, 3) to study student’s artistic creativity, and 4) to examine student’s satisfaction toward inductive approach. This is a One-Group Pre-test - Post-test experimental research. The samples gained from purposive sampling are Mattayomsuksa 3 (Grade 9) students at “Piboonbumpen” Demonstration School of Burapha University. The research tools are 1) 6 lesson plans basically developed by lesson study, 2) 30 sets of learning achievement test with difficulty index (p) between 0.33 to.80, discrimination (r) between 0.20 to 0.67, and reliability of 0.95, 3) creativity assessment form, and 4) satisfaction evaluation form. The statistics used for data analysis are percentage, mean (), standard deviation (S.D.), and t-test. The findings are as follow. First, the efficiency range of the developed lesson plan is 88.89/85.65 which is higher than the set standard (80/80). Second, the student’s learning achievement gained from the post-test is higher than that of the pre-test with the statistical significance of.05. Third, the student’s artistic creativity is in distinction level. Fourth, the satisfaction toward the approach falls into high level.